Playing with the big boys basketball, American imperialism, and subaltern discourse in the Philippines - Antolihao, Lou (Ateneo De Manila University Press, 2017)
""Playing with the Big Boys" traces the development of basketball in the Philippines from and educational to tool during the early period of American colonial rule in the early twentieth century to a ubiquitous national pastime".